Comparison of the cost of illness of primary liver cancer between Japan and Taiwan - Yinghui Wu; Kunichika Matsumoto; Ya-Mei Chen; Yu-Chi Tung; Tzu-Ying Chiu; Tomonori Hasegawa (Health Economics Review, 2020)
Background: Primary liver cancer (PLC) is the fifth and second leading cause of death in Japan and Taiwan, respectively. The aim of this study was to compare the economic burden of PLC between the two countries using the cost of illness (COI) method and identify the key factors causing the different trends in the economic burdens of PLC. Materials and methods: We calculated the COI every 3 years using governmental statistics of both countries (1996-2014 data for Japan and 2002-2014 data for Taiwan). The COI was calculated by summing the direct costs, morbidity costs, and mortality costs. We compared the COIs of PLC in both countries at the USD-based cost. The average exchange rate during the targeted years was used to remove the impact of foreign exchange volatility. Results: From 1996 to 2014, the COI exhibited downward and upward trends in Japan and Taiwan, respectively. In Japan, the COI in 2014 was 0.70 times the value in 1996, and in Taiwan, the COI in 2014 was 1.16 times greater than that in 1996. The mortality cost was the greatest contributor in both countries and had the largest contribution ratio to the COI increase in Japan. However, the direct cost in Taiwan had the largest contribution ratio to the COI decrease. Conclusions: To date, the COI of PLC in Japan has continuously decreased, whereas that in Taiwan has increased. Previous health policies and technological developments are thought to have accelerated the COI decrease in Japan and are expected to change the trend of COI of PLC, even in Taiwan.
Keywords: 330; Cost of illness; Health policy; Liver neoplasms; Medical economics; Public health